A triple band circularly polarized rectenna for RF energy harvesting. Issue 7 (3rd October 2019) - Singh, Neeta; Kanaujia, Binod Kumar; Tariq Beg, Mirza; Mainuddin,; Kumar, Sachin
ABSTRACT: In this paper, a triple band rectenna for Wi-Fi (2.4 GHz), Wi-MAX (3.5 GHz) and WLAN (5.2 GHz) application frequencies is proposed. The rectenna consists of a square-shaped circularly polarized antenna and a voltage doubler rectifier linked through a matching circuitry. A Schottky diode based voltage doubler rectifier and three stubs are used for the rectification of RF power to achieve high conversion efficiency. The impedance matching network provides a perfect matching between the sensing antenna and RF-DC rectifier. The rectenna maximum conversion efficiency realized is 85.6% at 3.5 GHz.